Association of polymorphisms in the CSN2, CSN3, LGB and LALBA genes with milk production traits in Holstein cows raised in Turkey - SOYUDAL, B.; ARDICLI, S.; SAMLI, H.; DINCEL, D.; BALCI, F. (Journal of the Hellenic Veterinary Medical Society, 2019)
A polymerase chain reaction-restriction fragment length polymorphism (PCR-RFLP) test was performed on DNA samples extracted from blood samples of 189 Holstein Friesian cows to detect genotypic distribution of polymorphic markers in the bovine beta-casein (CSN2), kappa-casein (CSN3), beta-lactoglobulin (LGB) and alfa-lactalbumin (LALBA) genes responsible for milk production traits. Statistical analysis was carried out using least square methods of the general linear model (GLM) procedure. CSN2 locus was significantly associated with the following traits: 305-day milk yield, days before peak milk production, fat percentage and protein yield. There was no significant effect of CSN3, LGB and LALBA markers on the traits analysed. These results suggested that CSN2 marker may be evaluated in selection programmes regarding not only milk content but also milk production.